Effect of The Proportion of Sorghum Flour: Wheat and Carrageenan on The Quality of Patin Fish Burger - Nurdin Dwiki Febrian; Jariyah; Winarti (Universitas Dr Soetomo, 2021)
Patty Burger is minced meat, shaped round, flattened, steamed first, and then fried in butter or grilled over coals. Patin fish meat was chosen because it is high protein and low fat, the use of proportions of sorghum flour and wheat flour to improve product quality so that it is not easily crushed, the addition of carrageenan as a stabilizer to improve texture. This study aimed to determine the effect of the proportion of sorghum flour and wheat with the addition of carrageenan on the quality of the patty burger of patin fish This study used a factorial Completely Randomized Design (CRD) with two factors, factor I the proportions of sorghum flour and wheat flour (60%:40%, 70%:30%, 80%:20%) and factor II carrageenan concentration (0, 5%, 1%, 1.5%). Data obtained were analyzed using ANOVA, if there was a significant difference between treatments, a 5% DMRT further test was carried out. This study showed a significant interaction with the observation parameters of moisture content, ash content, fat content, WHC, texture, starch content, food fiber, and hedonic organoleptic tests (aroma scores, color scores, taste scores). The best results were obtained in the A2B2 treatment, proportion of sorghum and wheat flour (70%:30%) with the addition of 1.0% carrageenan with the characteristics of water content 57.74%, protein content 14.47%, fat content 5.18%, texture 0.13 mm/gr/sec, WHC 16.50%, starch 17.43% and a score of 3.87 (like) for color 3.82 (slightly like) for taste and 3.75 (slightly like) for scent.